Pelatihan Pembuatan Media Pembelajaran dari Barang Bekas bagi Guru SD N 006 Tanjung Bungo - Romi Laspita; Afriza Rahma Rani; Indriyanto Indriyanto (Jurnal Pengabdian Masyarakat (abdira), 2022)
The implementation of this service is motivated by the lack of awareness of teachers about the importance of using learning media, lack of motivation of teachers to carry out learning using effective, efficient, creative, and innovative media, the inability of teachers to use learning media. Based on this, this service is carried out with the aim of providing an understanding of the importance of elementary science learning media, especially for the High Class, providing insight into the types of science learning media and making science learning media by utilizing used goods, especially the high class. The result of this service is that participants can understand, perform, and create and utilize learning media from used goods.